Comparison of Women’s Perceptions of Violent Extremism between Ambon City and Yogyakarta City - Ilela, Jean Evelyn; Afni Khafsoh, Nur; Jemmy Talakua, Rizard; Michelot Brun, Elenore (Jurnal Sosiologi Agama, 2024)
Women’s vulnerability to exposure to violent extremism must receive serious attention from all groups. This is because extremism spreads easily and quickly, especially with recruitment using social media which is very easy to reach many groups. The location situation and describing the typology of women’s perceptions of violent extremism in Ambon City and Yogyakarta City, and analyzing the factors that influence women’s perceptions of acts of extremism are the objectives of the research carried out. Approach The research method used is the Quantitative Approach using the Independent Sample t-Test. The results of the research show that the factors that influence perceptions on the Knowledge variable in Ambon City have an average of 41.97 and Yogyakarta City has an average of 26.41, then Action in Ambon City has an average of 34.09 and Yogyakarta City 33. 85, Attitudes in Ambon City have an average of 32.10 and Yogyakarta City 30.90, and Reasons in Ambon City have an average of 22.09 and Yogyakarta City 22.51. There are differences in women’s perceptions on the knowledge variable in Ambon City and Yogyakarta City. Women’s perceptions of extreme violence in Ambon City and Yogyakarta City are strongly influenced by the social context and experiences of conflict.